On Olfactory Research in Uzbek Linguistics (Zien Journal of Social Sciences and Humanities, 2023)
In this article, for the first time in Uzbek linguistics, the issues of smell and its impact on human thinking were researched, and the issues of smell and its expression and verbalization in non-verbal communication were considered on the basis of artistic text materials. First, the division of odors into natural and artificial odors, and then their separation into pleasant and unpleasant aspects according to their antonyms, was studied